Pre-shift anxiety and its factors influencing among nursing students during clinical placement in Universiti Sains Malaysia Health Campus - Ting, Veronica Lim Mei
The term pre-shift anxiety can be easily searched from website or webpage, this simply means that this kind of anxiety is existed in this century. Surprisingly, there has been no research done regarding this issue. Pre-shift anxiety is an anticipatory anxiety that is used to describe healthcare students or healthcare professionals experiencing anxiety symptoms right before starting their shift in the day. Pre-shift anxiety can cause the healthcare students or healthcare professionals to feel anxious and panic right before starting their work and eventually negatively affect their performance. In a worse-case scenario, this can in turn negatively affect the patient care and patient outcomes. Undeniably, pre-shift anxiety is a recurring problem in healthcare but sadly this issue has not been paid enough attention by the authorities. Therefore, this study aims to determine the level of pre-shift anxiety and its factors influencing (self-confidence and sense of belonging) among the nursing students during clinical placement in Universiti Sains Malaysia Health Campus. A total of 135 nursing students of Universiti Sains Malaysia participated in this study by answering self-administered questionnaire through Google Form sent to them. The collected data was analyzed through SPSS version 26.0. Sociodemographic characteristics, the level of pre-shift anxiety and the level of self-confidence and sense of belongingness were presented in descriptive statistics. Besides, the association between sociodemographic characteristics, self-confidence, and sense of belongingness with pre-shift anxiety was analyzed by Pearson’s Chi Square and Independent T test. Expectedly, most of the nursing students in Universiti Sains Malaysia Health Campus are experiencing high level of pre-shift anxiety. However, self-confidence and sense of belongingness are not the main factors that influence the students to have pre-shift anxiety. Nevertheless, the findings of this study provide insight for the healthcare authorities or healthcare schools regarding the issues of pre-shift anxiety among healthcare students and healthcare professionals. Therefore, appropriate action or strategies should be taken to solve this issue and reduce pre-shift anxiety in healthcare settings so that patient outcomes can be improved, and quality care can be delivered.